HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 1 PINGGIR KABUPATEN BENGKALIS - Eka Sapitri; Nurul Fauziah (Universitas Labuhanbatu, 2022)
This research is correlation research. This study aims to determine the relationship between self-efficacy and motivation to learn biology in class X SMA Negeri 1 PinggirÂ in the 2021/2022 school year. Observations, interviews, questionnaires, and documentation are the instruments utilized in data collecting. This study was carried out between July 18 and August 18, 2022. This study used a saturated sampling method as its sampling strategy.